GREEN SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL STUDIES OF MIXED LIGAND COMPLEXES OF Co (II), Ni (II) and V(III) METALS USING SOME AMINO ACIDS AS LIGANDS - Gwaram, N. S.; Salisu, A.; Manir, Muhammad (FUDMA JOURNAL OF SCIENCES, 2021)
Co (II), Ni (II) and V (III) metal complexes were synthesized mechanochemically using L-Leucine, L-Tyrosine and Creatinine as mixed ligands. The metals and the ligands were grounded using an agate mortar with a pestle. The compounds formed were characterized using their melting/decomposition temperature, solubility, magnetic susceptibility, conductivity measurement, Infrared analysis and scanning electron microscope (SEM). The Metal – ligand ratios were investigated via Job’s method of continuous variation. The shifts of bands (for instance 1693-1677 cm-1 to 1674-1607 cm-1) in C=O and the appearance of new bands in the complexes (683-669 and 713-750 cm-1 indicates the complexation. The lower conductivity measurement values (15.00 to 32.40) µS.cm-1 suggested the non-electrolytic nature of the complexes. The magnetic effective value of the metal complexes showed that all the three complexes are paramagnetic and octahedral. It was concluded that the amino acids (ligands) coordinated in a bidentate way through the nitrogen from the amino group and oxygen from carboxylate. The complexes were screened for their antimicrobial activities against two bacterial isolates (Streptococcus pneumoniae and Klebsiella pneumoniae). All the complexes exhibited good activity against the organisms